STRATEGI PEMERINTAH REPUBLIK INDONESIA GUNA MENINGKATKAN KEAMANAN WILAYAH PERBATASAN BERDASARKAN PERSPEKTIF SOSIAL PEMBANGUNAN - Putri, Lusy Riadina; Tanebet, Marck Buce (Institut Pemerintahan Dalam Negeri, 2023)
The national development of the Unitary State of the Republic of Indonesia (NKRI) aims to realize equal distribution of people's welfare throughout the region, including border areas where until now there are still problems related to welfare. The border area essentially has a very vital and strategic meaning, at least when viewed from 3 (three) points of view, namely: defense-security, economic-trade, and socio-cultural. Therefore, a strategy is needed to improve the security of border areas according to the social perspective of development. This study used qualitative descriptive method, with data collection using interviews, observation, and documentation. Data analysis techniques use triangulation. This research shows that the strategy that can be carried out by the Indonesian government in overcoming problems in order to improve border area security according to the social perspective of border development of the Republic of Indonesia (RI) – Democratic Republic of Timor Leste (RDTL) in Atambua, Belu Regency, East Nusa Tenggara Province, among others, through Economic Development, Infrastructure, Human Resource Development, Social Welfare Programs, Diplomacy and Regional Cooperation, Community Empowerment, Cultural and Social Security, Law Enforcement, and Social Security.